2004
DOI: 10.1002/sia.1846
|View full text |Cite
|
Sign up to set email alerts
|

The connection between hydrogen diffusion through a steel membrane and mechanism of the hydrogen evolution reaction

Abstract: The kinetics of the hydrogen evolution reaction (HER) on Armco iron and carbon steel have been studied in the C 2 H 4 (OH) 2 -H 2 O-HCl system. The addition of 5-10% water or 1-10 mM Na 2 HAsO 4 to the ethylene glycol solutions of HCl causes a transition from the Volmer rate determining step (rds) to the Tafel rds in the HER mechanism. According to experimental data, the rate of hydrogen diffusion through the carbon steel membrane does not depend on the rds nature of the HER. Theoretical analysis of the peculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…6. The H r form is characterized by a firmer bond with metal than the H s form what corresponds well to the results reported in [15,16]. Simultaneously, the bond energy of the H r form increases with increasing q (for instance, at the anodic polarization) faster than the energy of the H s form.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…6. The H r form is characterized by a firmer bond with metal than the H s form what corresponds well to the results reported in [15,16]. Simultaneously, the bond energy of the H r form increases with increasing q (for instance, at the anodic polarization) faster than the energy of the H s form.…”
Section: Discussionsupporting
confidence: 77%
“…An increase of the initial water concentration in the ethylene glycol solutions up to 2 wt% causes an essential modification of a character of the solvation effects without a change of the nature of the HER rds in the presence of both Na 2 HAsO 4 [16] and (NH 2 ) 2 CS [15]. With increasing the initial water concentration up to 2 wt% both the solvated forms of the protons (C 2 H 4 (OH) 2 The hydrogen overvoltage increase was determined by the independent and direct polarization measurements with use of the equilibrium hydrogen electrode in the same solution as a reference electrode [11,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Chatzidouros et al (2011) used in-situ electrochemical hydrogenation to study the effect of hydrogen on the fracture properties of the heat-affected zone of pipeline steel. Tsygankova et al (2004) investigated the relationship between hydrogen evolution on the metal surface and hydrogen diffusion in the metal using electrochemical hydrogenation method. Barnoush and Vehoff (2010) found that the effect of hydrogen on the micro-mechanical properties of the material was due to the reduction of the load required to promote the release of dislocations, using electrochemical hydrogenation and nanoindentation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the recombination rate constant, k 2 , in the KCNS presence conforms with the θ H decrease in comparison with the background solutions. Evidently the hydrogen diffusion into steel doesn't connect with the hydrogen surface coverage that was shown before (12).…”
Section: Ecs Transactions 2 (9) 1-9 (2007)mentioning
confidence: 94%